2016
DOI: 10.7314/apjcp.2016.17.s1.37
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude Towards Tobacco Smoking among 13-15 Year-Old School Children in Viet Nam - Findings from GYTS 2014

Abstract: Studies have shown that smoking is a learnt behavior, often initiated during adolescence. This paper aims to describe tobacco-related knowledge, attitude and associations among school adolescents aged 13-15 with exposure to anti-smoking information. Using data from the Global Youth Tobacco Survey (GYTS) in Viet Nam, 2014, knowledge was measured through 4 questions about tobacco use, and attitude was assessed through 3 questions on personal, social and environmental aspects. Students giving most anti-tobacco re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
(10 reference statements)
0
7
0
2
Order By: Relevance
“…Attitude toward smoking was defined as a person's summary evaluation of smoking (the attitude object), which might be "positive" (good) or "negative" (bad) (Huong et al, 2016). Study participants reported their global evaluation toward smoking using a semantic differential measure of smoking such as "nice versus awful,""pleasant versus unpleasant," and "fun versus not fun" (Macy et al, 2012).…”
Section: Attitude Toward Cigarette Smokingmentioning
confidence: 99%
“…Attitude toward smoking was defined as a person's summary evaluation of smoking (the attitude object), which might be "positive" (good) or "negative" (bad) (Huong et al, 2016). Study participants reported their global evaluation toward smoking using a semantic differential measure of smoking such as "nice versus awful,""pleasant versus unpleasant," and "fun versus not fun" (Macy et al, 2012).…”
Section: Attitude Toward Cigarette Smokingmentioning
confidence: 99%
“…Học sinh cho rằng hút thuốc sẽ mang lại lợi ích, chẳng hạn như tăng cường sự nổi tiếng và gắn kết xã hội, hoặc cải thiện tâm trạng làm tăng khả năng hút thuốc [4]. Tiếp cận với truyền thông phòng chống tác hại thuốc lá được xem là một trong những yếu tố bảo vệ, tăng thái độ tiêu cực với việc sử dụng thuốc lá [5]. Nghiên cứu về các nguồn thông tin và khả năng tiếp cận của học sinh với các nguồn thông tin này sẽ cung cấp bằng chứng cho các biện pháp can thiệp truyền thông.…”
Section: đặT Vấn đềunclassified
“…Với các quan điểm khác như "Hút thuốc lá làm cho bạn ít hấp dẫn hơn, ít bạn bè, thiếu sự thoải mái trong các bữa tiệc hay tác hại" thì tỷ lệ đồng ý cũng cao hơn. Kết quả này tương đồng với kết quả trong nghiên cứu của tác giả Wilkinson năm 2009 [6] và kết quả nghiên cứu điều tra tình hình sử dụng thuốc lá trong học sinh từ 13 đến 15 tuổi năm 2014 [5] Tỷ lệ học sinh nhìn thấy các thông tin về tác hại của thuốc lá và thông tin về việc cấm người dưới 18 tuổi mua/bán/sử dụng các sản phẩm thuốc lá dao động từ 25,2% đến 71,5%. So sánh các nguồn thông tin cho thấy phương tiện thông tin đại chúng như tivi, đài, internet, pano, áp phích, báo, tạp chí hay phim ảnh là nguồn thông tin có tỷ lệ tiếp cận cao nhất, cũng có thể xem là nguồn thông tin chính phổ biến các kiến thức về tác hại thuốc lá cho học sinh.…”
Section: Bàn Luậnunclassified
“…Research by (Nguyen et al, 2017) describe smokiness as a behavior that is occupied. The existence of a mandate and coverage of anti-smoking by various means can promote correct insight regarding the effects of smoking and the perception of adolescents about smoking.…”
Section: Introductionmentioning
confidence: 99%